THE TEACHING OF WRITING RECOUNT TEXTS BY UTILIZING PADLET - Asep Saepuloh; Vina Aini Salsabila (Indonesian EFL Journal, 2020)
Writing has always been beneficial for those who master it. Albeit its virtues, it is subject to investigation due to issues concerning its derisory tasks, its complexity, and its arid learning activities. Based upon the issues, this study is aimed at portraying how English teachers teach students writing recount texts by integrating Padlet into their classroom. Involving one English teacher and a class of 25 students, this study obtained the data through observation of four class meetings. The data were then analyzed qualitatively to depict thoroughly the teaching practice of the teacher as Padlet was deployed in the classroom. The analysis resulted in findings vis-à-vis the integration of Padlet and the teacher’s ways of integrating Padlet, that the integration of technology is categorized into some levels. The findings to some extent conform to previous studies that the integration of technology has been prevalent among English teaching in general. It is therefore suggested that teachers maintain the integration of technology while keep on fostering the accompanying capability of integrating it. Keywords: writing; recount texts; Padlet; technology integration; digital teaching media.